Comparative Analysis of Renewable Energy Technologies in Poland: Photovoltaic Dominance and Sectoral Transitions (2014-2024) - Arkadiusz WEREMCZUK; Mariusz CHĄDRZYŃSKI; Sylwester KOZAK (Communications of International Proceedings, 2025)
The research examines the extent of structural transformation in Poland's renewable electricity sector between 2014 and 2024 when photovoltaics (PV) and wind power replaced biomass as the fundamental components of national renewable energy production. The current research provides policy drivers and cost trends and technology-specific deployment data yet lacks integrated indicator-based assessments of structural change and technology interactions in Poland's renewable portfolio. The research creates a standardized yearly database for five technologies which includes PV and wind and solid biomass and biogas and hydropower through data from ARE and URE and PSE and PSE and IRENA and Eurostat. The research design uses compound annual growth rates (capacity and generation) and three additional indexes (Efficiency Index and Structural Share Index and Structural Change Index) and Pearson correlations between sectoral time series to measure both scale effects and substitution–complementarity patterns. The study demonstrates that renewable capacity installation grew from 5.8 GW to 32.3 GW while power generation expanded from 19.3 TWh to 48 TWh with a total structural change index of 45.2%. The renewable electricity production in 2024 reached 80% through PV and wind power systems while PV systems generated 60% of all new electricity output. The correlation pattern shows that PV replaced biomass in the market (r = −0.92) while PV and wind power showed positive growth patterns (r = +0.85). The research establishes a new solar–wind power system through definition-specific indicators which enable researchers to evaluate Poland's transition against other European Union countries.
Keywords: renewable energy transition; photovoltaics (PV) dominance